CLONING AND CHARACTERIZATION OF AUXIN EFFLUX CARRIER GENES ECPIN1C AND ECPIN1D FROM FINGER MILLET ELEUSINECORACANA SUBSP. CORACANA - T. K. Mohanta; D. Yadav (Journal of Animal and Plant Sciences, 2019)
Auxin is one of the most important plant hormone and its transport from the tip of the plant towards the root tip is mediated by auxin transporters. There are four different types of auxin transporters reported so far in plant kingdom. They are auxin influx carrier (AUX/LAX), auxin efflux carrier (PINs), ATP-binding cassette transporters (ABCBs), and PIN-Likes (PILS). Auxin efflux carrier mediates long as well as short distance auxin transport and plays critical role in root development in plants. Lack of genome sequence data in the crop plant Eleusine coracana hampers the advanced study in root development. Therefore, we cloned two auxin efflux carrier genes EcPIN1c and EcPIN1d from the orphan plant E. coracana. In-silico analysis revealed EcPIN1c and EcPIN1d were encoded for 1677 bp and 1716 bp, respectively. EcPIN1c and ECPIN1d were found to be localized to the plasma membrane.  Multiple sequence alignment revealed presence of several conserved motifs in EcPIN1c and EcPIN1d.  Functional motif analysis revealed the presence of thirty-three functional motif in EcPIN1c and thirty-one in EcPIN1d protein. Phylogenetic study showed EcPIN1c and EcPIN1d grouped with the PIN1 genes of Oryza sativa, suggesting these genes are monocot specific. Expression analysis showed significant up-regulation of EcPIN1c genes in leaf and root tissue at different developmental stages, suggesting their important role in plant development.
Keywords: Auxin; influx carrier; efflux carrier; PIN; transmembrane domain; myristoylation; phosphorylation